Kepuasan Petani Ikan Nila terhadap Kemitraan Agribisnis dengan UD. Maju Bersama di Kecamatan Seginim Kabupaten Bengkulu Selatan - Ahmad Akbar; Herri Fariadi; Ana Nurmalia (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The abundant harvest in Babatan Ilir Village has created marketing challenges for tilapia farmers. To address this issue, the farmers have established a partnership with UD Maju Bersama, which provides seeds, feed, and business capital, as well as purchases their production output. This study aims to analyze the partnership pattern between UD Maju Bersama and tilapia farmers in the grow-out phase of tilapia farming, as well as to assess the level of farmer satisfaction with the agribusiness partnership in Babatan Ilir Village, Seginim District, South Bengkulu Regency. This research employs a quantitative descriptive method using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results show that one of the partnership models between tilapia farmers and UD Maju Bersama is the Agribusiness Operational Cooperation (KOA) scheme. Under this model, UD Maju Bersama assists farmers in marketing their harvest and provides feed, seeds, and necessary medicines. Additionally, in accordance with the agreement, farmers who provide land and labor are required to sell their harvest to UD Maju Bersama. Using the IPA method, the study found an average satisfaction level of 88.86%, while the Customer Satisfaction Index (CSI) of tilapia farmers toward UD Maju Bersama reached 82.67%. This indicates that the CSI falls within the range of 81% to 100%, which is categorized as